International REACH forgiveness intervention: a multisite randomised controlled trial - Tyler J Vanderweele; Nicole Rodriguez; Richard G Cowden; Man Yee Ho; Everett L Worthington; Andrea Ortega Bechara; Zhuo Job Chen; Elly Yuliandari Gunatirin; Shaun Joynt; Viacheslav V Khalanskyi; Hennadii Korzhov; Ni Made Taganing Kurniati; et al. (BMJ Public Health)
Objectives To determine whether a brief self-directed forgiveness workbook intervention could alter forgiveness, depression symptoms, and anxiety symptoms.Design A multisite randomised waitlist-controlled trial was conducted among 4598 participants. Recruitment occurred from 11 February 2020 to 30 September 2021. Final follow-up occurred on 25 October 2021.Setting Participants were recruited from community-based samples in sites in Colombia, Hong Kong, Indonesia, South Africa, and Ukraine.Participants Individuals (n=7837) were screened for eligibility. For inclusion, participants needed to be ≥18 years and have experienced an interpersonal transgression. The analytic sample consisted of n=4598 participants, median age 26 and 73% female.Interventions At each site, participants were randomly assigned to either immediate receipt of a self-directed forgiveness workbook intervention, or to receipt after a 2 week delay.Main outcomes measures The primary outcomes were unforgiveness (Transgression-Related Interpersonal Motivations Inventory-18), depression symptoms, and anxiety symptoms (Brief Symptom Inventory-18) measured at 2 weeks following intervention assignment.Results At 2 weeks follow-up, unforgiveness was lower among the immediate-treatment group compared with the delayed-treatment group (standardised mean difference=−0.53 (95% CI=−0.58 to –0.47)); similar patterns were found for depression (standardised mean difference=−0.22 (95% CI=−0.28 to –0.16)) and anxiety symptoms (standardised mean difference=−0.21 (95% CI=−0.27 to –0.15)).Conclusions A brief workbook intervention promoted forgiveness and reduced depression and anxiety symptoms. The promotion of forgiveness with such workbooks has the potential for widespread dissemination to improve global mental health.Trial registration number NCT04257773.